2019
DOI: 10.1186/s12882-019-1520-x
|View full text |Cite
|
Sign up to set email alerts
|

The association of neighborhood racial mix and ED visit count in a cohort of patients on hemodialysis

Abstract: Background Neighborhood racial mix is associated with dialysis facility performance metrics and mortality outcomes in patients on hemodialysis. We explored the association of neighborhood racial mix with emergency department (ED) visits in patients receiving hemodialysis. Methods Using Looking Glass (Montefiore’s clinical database) we identified a cohort of patients on hemodialysis with an index ED visit at any of 4 Montefiore Hospital locations, between January 2013 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Medical records were reviewed for COVID-19 status (based on RT-PCR testing of nasopharyngeal samples), demographics (age and sex), socioeconomic status expressed as standard deviations from the New York State mean income based on census tract data ( 20 ), lab tests, history of PVD, presenting symptoms, ICU stay and outcomes of death or leg amputation. Diagnostic test used to detect SARS-CoV-2 infection was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Medical records were reviewed for COVID-19 status (based on RT-PCR testing of nasopharyngeal samples), demographics (age and sex), socioeconomic status expressed as standard deviations from the New York State mean income based on census tract data ( 20 ), lab tests, history of PVD, presenting symptoms, ICU stay and outcomes of death or leg amputation. Diagnostic test used to detect SARS-CoV-2 infection was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Thus the IRR represented in this manuscript is similar to the range of reported associations for other clinical and demographic factors that are associated with dialysis related hospitalization and/or mortality. 29 We observed that those receiving treatment in communities with substantial proportions of Black residents had fewer comorbidities, had lower rates of AVF use, and shorter dialysis sessions.…”
Section: Discussionmentioning
confidence: 69%
“…33,34,43,44 In previous studies, Black men living in communities with sizable Black populations were shown to have lower access to pre-ESKD nephrology care, and experience lower quality of dialysis treatments, both of which were thought to mediate their worse outcomes. 29,45 Furthermore, Black men have been shown to suffer from multiple structural inequities that amplify the adverse impact of economic disadvantage on their health outcomes, and thus may not be able overcome this disadvantage by relying solely on the higher social capital and support they may receive within communities with substantial proportions of Black residents. 16,17 Thus, Black men in communities with sizable Black populations appear especially vulnerable to the socioeconomic attributes of their communities with respect to their health outcomes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…54 Education was not a predictor of fatigue symptoms, 74 hospital outcomes, or dialysis facility ratings. 55 In a patient survey conducted by Setodji et al, there was inconclusive evidence that education affected treatment. 50…”
Section: Educationmentioning
confidence: 99%